Metabolism of Arginine by Aging and 7 Day Old Pumpkin Seedlings - Splittstoesser, Walter E. (1969)
The metabolism of arginine by etiolated pumpkin (Cucurbita moschata) seedlings was studied over various time and age intervals by injecting arginine-U-(14)C into the cotyledons. At most, 25% of the (14)C was transported from the cotyledon to the axis tissue and the amount of this transport decreased with increasing age of the seedlings. The cotyledons of 25 day old plants contained 60% of the administered (14)C as unmetabolized arginine. Little (14)C was in sugars and it appeared that arginine was the primary translocation product. Time course studies showed that arginine was extensively metabolized and the labeling patterns suggest that different pathways were in operation in the axis and cotyledons. The amount of arginine incorporated into cotyledonary protein show that synthesis and turnover were occurring at rapid rate. Only 25% of the label incorporated into protein by 1.5 hr remained after 96 hr. The label in protein was stable in the axis tissue. By 96 hr 50% of the administered label occurred as (14)CO(2) and it appeared that arginine was metabolized, through glutamate, by the citrio acid cycle in the cotyledons. The experiments showed that an extensive conversion of arginine carbon into other amino acids did not occur.